Piezo‐Phototronic Effect Enhanced Flexible Solar Cells Based on n‐ZnO/p‐SnS Core–Shell Nanowire Array. Issue 1 (7th July 2016) - Zhu, Laipan; Wang, Longfei; Xue, Fei; Chen, Libo; Fu, Jianqiang; Feng, Xiaolong; Li, Tianfeng; Wang, Zhong Lin
Abstract : The piezo‐phototronic effect is about the enhanced separation, transport, and recombination of the photogenerated carriers using the piezoelectric polarization charges present in piezoelectric‐semiconductor materials. Here, it is presented that the piezo‐phototronic effect can be effectively applied to improve the relative conversion efficiency of a flexible solar cell based on n‐ZnO/p‐SnS core–shell nanowire array for 37.3% under a moderate vertical pressure. The performance of the solar cell can be effectively enhanced by a gentle bending of the device, showing its potential for application in curly geometries. This study not only adds further understanding about the concept of increasing solar energy conversion efficiency via piezo‐phototronic effect, but also demonstrates the great potential of piezo‐phototronic effect in the application of large‐scale, flexible, and lightweight nanowire array solar cells. Abstract : A flexible solar cell based on n‐ZnO/p‐SnS core–shell nanowire array is fabricated. The piezo‐phototronic effect is applied to effectively improve the relative conversion efficiency of the solar cell under a moderate vertical pressure or by a gentle bending of the device, showing its potential for application in curly geometries.